2022
DOI: 10.3928/1081597x-20211109-01
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficacy of Four Diagnostic Devices and Four Nomograms in Posterior Chamber Phakic Intraocular Lens Size Selection

Abstract: PURPOSE: To assess the efficacy of different devices and nomograms in predicting the most optimal Implantable Collamer Lens (ICL) (STAAR Surgical) size. METHODS: This retrospective study includes 73 patients (142 eyes) who underwent ICL placement surgery. Anterior segment measurements were obtained by the OPD-Scan III (Marco), the Lenstar LS 900 (Haag-Streit AG/Alcon Laboratories, Inc), the Galilei G4 (Ziemer), and the VuMax ultrasound biomicroscopy dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Moreover, ophthalmologists usually use the STAAR manufacturer’s online calculator to determine ICL size. This method is based on the preoperative WTW and ACD of the patient, and the indicated ICL size is generally too large, resulting in a high proportion of patients with an excessive postoperative vault [ 30 ]. Therefore, more attention should be paid to angle narrowing and suspicious angle-closure caused by an abnormal vault after ICL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ophthalmologists usually use the STAAR manufacturer’s online calculator to determine ICL size. This method is based on the preoperative WTW and ACD of the patient, and the indicated ICL size is generally too large, resulting in a high proportion of patients with an excessive postoperative vault [ 30 ]. Therefore, more attention should be paid to angle narrowing and suspicious angle-closure caused by an abnormal vault after ICL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with previous studies, STAAR's nomogram was found to indicate ICL sizes larger than the ideal size, potentially leading to oversizing complications, such as angle-closure glaucoma. 26,27 The accuracy of ET and RF models in predicting the vaulting value, with a precision of ±250 μm, was 94% and 90%, respectively. By developing classifiers, this accuracy improved to an excellent value of 98%, which was possible as the classifiers predict a discrete output (ICL size), rather than a continuous output (vault size), with a lower dependence on nondeterministic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Rancons ( 6 ) and Zhang ( 16 ) used WTW and ACD to select the lens size based on the STAAR formula, and 53 and 65%, respectively, of the subjects achieved postoperative vault in the ideal range. Moshirfar ( 17 ) used STS and lens rise to select the lens size, and 77% patients achieved the ideal vault. Malyugin ( 18 ) used PTP (iris pigment end to iris pigment end distance) for size selection, and 55% of the patients achieved the ideal vault after surgery.…”
Section: Discussionmentioning
confidence: 99%